Perspektiven der Psychoanalyse. Einblicke in die psychoanalytische Behandlung und die empirische Forschung - Giampieri Deutsch, Patrizia (Bollettino Filosofico, 2022)
The paper investigates empathy within the framework of the psychoanalytic treatment as well as in empirical research in psychoanalysis and cognitive science. Within the configuration of the psychoanalytic treatment, a theoretical and clinical outline of the phenomena of empathy turns out to be everything but simple, due to the interplay within the psychoanalytic process between the transference of the patient, which is characterized by illusions and self-deceptions, and the countertransference of the analyst. On the other hand, empathy as well as the analytic relation and the therapeutic alliance – or working alliance – constitute those moments of reality in a psychoanalytic treatment, which are far less distorted by the mirages and delusions of the transference. Therefore, by dealing with the topic of empathy, also the analytic relation and real therapeutic alliance should be taken into account. The paper will also explore feasible intersections between recent psychoanalytic approaches to empathy and current phenomenological studies on this topic. Finally, following the investigation of the topic in the frame of reference of theoretical and clinical psychoanalysis, also the psychoanalytic empirical research on empathy of Lester Luborsky and Peter Fonagy as well as the cognitive research of Simon Baron-Cohen on this topic will be considered. Keywords: Cognitive Research, Empathy, Psychoanalytic Empirical Research, Psychoanalytic Relation, Therapeutic/Working Alliance